Exploratory analysis of molecular traits of the mitochondrial DNA of leafcutting ants to infer taxonomic characters towards an integrative taxonomy - Perpetua Ndubuisi Onyinyechi; Natália Martins Travenzoli; Maykon Passos Cristiano; Danon Clemes Cardoso (Journal of Hymenoptera Research)
Accurate systematic classification of biodiversity is fundamental for ecological and evolutionary studies, especially in a world where biodiversity is increasingly reduced and threatened. In the present study we propose using exploratory analysis of genetic markers to obtain additional information from the comparison of sequences among species as molecular traits (MTs). These molecular traits can in turn provide independent information for integrative taxonomy, aiding genus-level circumscriptions. Therefore, we use the leafcutting ant genera Amoimyrmex Cristiano et al., 2020, Atta Fabricius, 1804 and Acromyrmex Mayr, 1865 as models to evaluate a mitochondrial genome fragment regularly applied in phylogenetic and evolutionary studies. Bioinformatic analysis revealed shared structural evidence between species that can serve as diagnostic characters, distinguishing them from other species and supporting the classification of the three genera of leafcutting ants. The molecular features of the mitogenome segments, along with other traits such as chromosome number, karyotype features, molecular phylogeny, and morphological data can be used in an integrative framework to access biodiversity and purpose taxonomic hypothesis.